Project management for dummies - Portny, Stanley E. (Stanley Erwin) (--For dummies., 2007)
Track your progress and keep everyone in the know. Overcome scheduling challenges. Today's projects are more complex and technically challenging. How do you lead one successfully from start to finish? This practical guide gives you the tools you need to deal with schedules, budgets, and deadlines while keeping your cool under pressure.